A Mathematical Model for Dehydration by Successive Pressure Drops: Simulation of Discarded Potatoes Dehydration - Gutierrez-Pacheco, Sebastian; Palacios, Joahnn H; Parra-Coronado, Alfonso; Godbout, Stéphane (Journal of Food Technology Research, 2021)
Dehydration by Successive Pressure Drops (SPD) is a process with high potential for treating heat-sensitive materials; this includes agro-industry by-products. However, the response of drying kinetics to operating conditions of SPD is not fully understood. The present manuscript refers to mathematical simulations to describe drying kinetics of discarded potatoes using SPD. While there are numerous theoretical, semi-theorical and empirical mathematical models, the selection of the appropriate model is a rigorous process. In this paper, the Thompson thin-layer semi-theoretical model was chosen since the assumptions for this model (e.g., product is arranged in thin layers) are fulfilled for the SPD. As a result of mathematical simulation, it was possible to describe the drying kinetics in terms of the major parameters of SPD namely pressurizing level (Pa) and the Frequency of Pressure Drop (FPD). The dehydration by SPD allows the removal of water from the material, mainly at the pressure drop. If this stage occurs more frequently, the drying rate increases. The model developed describes at less 91% of the variability of the experimental data. It is recommended to use high FPD and Pa equals to 0.50 MPa.